2006
DOI: 10.1051/forest:2005095
|View full text |Cite
|
Sign up to set email alerts
|

Tension wood occurrence in three cultivars of Populus × euramericana. Part I: Inter-clonal and intra-tree variability of tension wood

Abstract: -The main wood quality problem affecting poplar trees is tension wood occurrence associated to end-splits after felling, distortions of products, woolly wood, etc. The objective of this study was to estimate the occurrence of tension wood by using the external shape of the stem and the 3D distribution of annual growth rings. This paper is the first of two papers and presents the inter-clonal and intra-tree tension wood variability. A clear clonal-effect was observed on tension wood area percentage (I-MC>I214>L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
(23 reference statements)
2
13
0
Order By: Relevance
“…This was experimentally proven by Jourez et al [11] for P-euramericana cv 'Ghoy'. Badia et al [1,2] reported different patterns of tension wood distribution between clones. They also stated that tension wood extent is highest at the tree base, which is also reflected in the data presented in Table II.…”
Section: Relationships Between Tension Wood Proportion Heartwood Andmentioning
confidence: 99%
“…This was experimentally proven by Jourez et al [11] for P-euramericana cv 'Ghoy'. Badia et al [1,2] reported different patterns of tension wood distribution between clones. They also stated that tension wood extent is highest at the tree base, which is also reflected in the data presented in Table II.…”
Section: Relationships Between Tension Wood Proportion Heartwood Andmentioning
confidence: 99%
“…When trees have to restore their verticality after some accidental leaning (or partial uprooting), they will produce a rather wide sector of reaction wood on the lower side of the stem for gymnosperms (compression wood), on the upper side for angiosperms (tension wood) [2,3,19,25]. Due to the usual higher growth rate in the reaction wood sector, the total volume of reaction wood in a log can be significant [16,33].…”
Section: Introductionmentioning
confidence: 99%
“…However, as shown by Clair et al (2003) in research on chestnut, rapid growth in some hardwoods can generate an increase in the amount of reaction wood in the stem thereby reducing the economic potential of the resource due to increased shrinking/swelling and distortion of timber in service. Furthermore, previous studies in poplar have shown that the proportion of reaction wood can vary from 7 to 40% depending on the clone (Badia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of reaction wood is associated with environmental conditions experienced by the tree during its development (Badia et al, 2006). In the case of an environment characterised by the presence of strong wind, the tree will develop a tendency to produce reaction wood to change its centre of gravity so as to bring the stem to a vertical position (forming a curve).…”
Section: Introductionmentioning
confidence: 99%